2009
DOI: 10.2460/ajvr.70.5.604
|View full text |Cite
|
Sign up to set email alerts
|

Use of signal analysis of heart sounds and murmurs to assess severity of mitral valve regurgitation attributable to myxomatous mitral valve disease in dogs

Abstract: Most of the investigated sound variables were significantly associated with severity of MR, which indicated a powerful diagnostic potential for monitoring MMVD. Signal analysis techniques could be valuable for clinicians when performing risk assessment or determining whether special care and more extensive examinations are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…In addition, one study showed a good correlation between MRA/LA and severe MR, despite the limitations of this method (Muzzi et al, 2003). Another study demonstrated that MRA and the intensity of the heart murmur were significant predictors of an increase in LA diameter (Olsen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, one study showed a good correlation between MRA/LA and severe MR, despite the limitations of this method (Muzzi et al, 2003). Another study demonstrated that MRA and the intensity of the heart murmur were significant predictors of an increase in LA diameter (Olsen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, O'Connor et al (1999) with the aim to identify risk factors associated with in-hospital mortality among patients undergoing percutaneous coronary interventions demonstrated that with the use of multivariate prediction/analysis the calculation of the risk of in-hospital mortality after a percutaneous coronary intervention was feasible and accurate, and may be useful for patient counseling and for improvement of quality purposes. In another study, Matheny et al (2005) evaluated the discrimination and calibration of mortality risk prediction models (logistic regression) in interventional cardiology and obtained positive results with the use of this method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations